2014
DOI: 10.2807/1560-7917.es2014.19.11.20736
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of multidrug-resistant tuberculosis in a low-incidence setting, Switzerland, 2006 to 2012

Abstract: The goal of the present study was to examine the transmission dynamics of multidrug-resistant tuberculosis (MDR-TB) in Switzerland. Between 2006 and 2012, a total of 49 MDR-TB cases were reported to the Swiss Federal Office of Public Health, 46 of which were of foreign origin. All 49 initial strains were evaluated by molecular epidemiologic methods at the Swiss National Reference Centre for Mycobacteria. In 43 strains, unique DNA fingerprint patterns were identified. Twelve strains were grouped into six cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…The low proportion of true transmission clusters among immigrants in our study was further supported by the weighted analysis of predictors of transmission, which showed that foreignborn TB patients tended to be less likely than Swiss-born patients to be involved in true clusters. Of note, the clustering proportion among immigrants is remarkably similar to previous observations among immigrant patients with multidrug resistance diagnosed in Switzerland, which showed a clustering proportion of 8% (compared to 7% in our study) on the basis of standard genotyping and contact tracing (30).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The low proportion of true transmission clusters among immigrants in our study was further supported by the weighted analysis of predictors of transmission, which showed that foreignborn TB patients tended to be less likely than Swiss-born patients to be involved in true clusters. Of note, the clustering proportion among immigrants is remarkably similar to previous observations among immigrant patients with multidrug resistance diagnosed in Switzerland, which showed a clustering proportion of 8% (compared to 7% in our study) on the basis of standard genotyping and contact tracing (30).…”
Section: Discussionsupporting
confidence: 76%
“…MIRU-VNTR typing clusters were defined as a group of isolates with identical MIRU-VNTR typing and spoligotyping patterns (9). In addition, we used IS6110 restriction fragment length polymorphism (RFLP) patterns when they were available from the National Center for Mycobacteria (30). RFLP has a higher resolution than MIRU-VNTR typing, particularly for strains of the Beijing genotype.…”
Section: Methodsmentioning
confidence: 99%
“…Most notably, the patient never received clofazimine. Genotyping using 24-locus mycobacterial interspersed repetitive unit variable number tandem repeats did not identify differences between the post-relapse and the previous isolates from 2011, indicating a common clonal origin of these isolates [7]. Recently, HARTKOORN et al [8] described a mechanism of cross-resistance between clofazimine and bedaquiline in in vitro-selected mutants due to mutation in the Rv0678 regulatory gene resulting in upregulation of the MmpL5 efflux pump gene.…”
Section: To the Editormentioning
confidence: 99%
“…A molecular surveillance study in Switzerland including all 49 MDR-TB strains identified in the period 2006 to 2012, showed that 12 strains were grouped into six clusters [7]. In-country transmission was likely in four clusters.…”
mentioning
confidence: 99%
“…Also, even though more invasive, fine-needle aspiration biopsy has proved to be useful for collecting samples in children with a peripheral lymph-node mass [16]. In addition to facilitating the diagnosis of TB and drug resistance, strains obtained from positive cultures can also be subjected to molecular typing and provide valuable information about transmission of TB such as demonstrated in several studies in this issue [6,7,8].…”
mentioning
confidence: 99%